The Soteriology of Leo the Great. By Bernard Green - Keating, Daniel A. (The journal of theological studies, 2009)
Leo the Great has been a vastly underrated and underappreciated figure in modern scholarship. His theology is normally considered derivative and uninteresting, and his role in the christological controversy surrounding the Council of Chalcedon is usually judged to have been unhelpful at best. In this gracefully written study of soteriology in Leo, Bernard Green sounds a very different note. The first full-length English study of Leo in sixty years, The Soteriology of Leo the Great offers an intensive diachronic study of Leo's sermons and letters, with the aim of bringing ‘Leo back into the limelight’ and offering ‘an invitation to others to look at him afresh’ (p. vii).